COLLABORATION OF CENTRAL, REGIONAL, AND COMMUNITY GOVERNMENTS IN THE IMPLEMENTATION OF SCHOOL DEMOCRACY IN THE ERA OF DECENTRALIZATION OF EDUCATION - Antonius Totok Priyadi; Khairullah; F. Devi Kurnia (Adisam Publisher, 2025)
This study explores the dynamics of collaboration among the central government, local government, and community in implementing democratic principles in schools within the context of educational decentralization in Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and policy document analysis. The findings reveal that the central government maintains a dominant role as regulator, the local government exercises adaptive implementation, and the community participates as partners in decision-making and oversight. However, democratic practices in schools remain limited due to strong central control, uneven local capacities, and symbolic community participation. These results highlight the importance of multi-level governance in education, emphasizing that the democratization of schools requires not only national policy but also strengthened local leadership and meaningful community engagement. The study contributes to the theoretical debate on decentralization and democracy in education while providing practical insights for policy design toward more inclusive and accountable school governance.